Comprehensive Analysis of Adverse Events Associated With SGLT2is: A Meta-Analysis Involving Nine Large Randomized Trials - Qiu, Mei; Zhao, Li-Min; Zhan, Ze-Lin (Frontiers in Endocrinology, 2021)
Recently, Lin and colleagues assessed the safety of sodium-glucose cotransporter 2 inhibitors (SGLT2is) by a meta-analysis [1], in which the authors assessed 16 kinds of adverse events (AE) reported in the published articles based on 10 randomized controlled trials. We conducted a further meta-analysis and targeted the association between use of SGLT2is and occurrences of various kinds of serious AE published in the Clinical Trials website (clinicaltrials.gov). Our meta-analysis revealed that use of SGLT2is was not significantly associated with occurrences of 980 kinds of serious AE but was significantly associated with lower risks of 29 kinds of serious AE, especially including several important respiratory diseases (e.g., asthma, chronic obstructive pulmonary disease, sleep apnoea syndrome, and pneumonia). These findings may cause more studies to evaluate the possibilities of gliflozins being used for prevention of these specific diseases.